Dance, multilingual repertoires and the Italian landscape: asylum seekers' narratives in an arts-based project. (4th March 2022) - Ciribuco, Andrea
ABSTRACT: This article examines the impact that an arts project had on the relationship between a group of asylum seekers and the Italian town where they live. The project brought together local youth and asylum seekers to engage in dance workshops and video-making workshops. This article combines interviews with project participants and teachers with an analysis of their artistic output. In doing so, it analyses how the multimodal nature of the activities enabled participants to communicate their concerns and aspirations without necessarily using the Italian language – emphasizing the body as a communicative resource and placing it in dialogue with the landscape. Questo studio esamina l'impatto che un progetto artistico ha avuto sulla relazione fra un gruppo di richiedenti asilo e la città italiana dove vivono. Il progetto ha messo in contatto giovani del luogo con richiedenti asilo in un workshop di danza e cinematografia. Il presente studio include interviste a partecipanti e insegnanti del progetto, e l'analisi della loro produzione artistica. La natura multimodale delle attività ha consentito ai partecipanti di comunicare le proprie speranze e preoccupazioni senza necessariamente usare la lingua italiana – mettendo in risalto il corpo come risorsa comunicativa, e ponendolo in relazione con il paesaggio circostante.